Efektivitas Strategi Program Desa Sadar Zakat Dalam Meningkatkan Kesadaran Masyarakat Terhadap Zakat: Studi Kasus Desa Sadar Zakat Kalimantan Utara - Yani Safariaty; Saiful Anwar (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2026)
This study aims to analyze the effectiveness of the Desa Sadar Zakat Program strategy in increasing public awareness of zakat in Desa Sadar Zakat, Sebatik Timur, Nunukan Regency, North Kalimantan. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the Desa Sadar Zakat Program strategy, which involves the active role of Islamic religious counselors, collaboration with Zakat Collection Units (UPZ), and educational as well as social approaches, has proven effective in enhancing public awareness to fulfill zakat obligations. This is evidenced by a significant increase in the collection of zakat, infaq, and alms (ZIS) funds in Sebatik Timur over the years.